Selected paper from 6th International Conference on Renewable Energy Sources (ICoRES 2019) - Jewiarz, Marcin (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Thank you for reaching for this book. It is a summary of the research presented at the 6th International Conference on Renewable Energy Sources (ICORES19), which took place in Krynica, Poland, in June 2019. This event is the most recognizable scientific meeting connected to RES in Poland. From the very beginning, this conference has been a unique occasion for gathering Polish and international researchers' perspectives on renewable energy sources and balancing them against governmental policy considerations. Accordingly, the conference has also offered panels to discuss best practices and solutions with local entrepreneurs and federal government bodies. The meeting attracts not only scientists but also industry representatives, as well as local and federal government personnel. We are open to new and fresh ideas concerning renewable energy, which is why so many scientists from Central and Eastern Europe visit Krynica to discuss the "Green Future" of this region. In 2019, the conference was organized by the University of Agriculture in Krakow, in cooperation with the AGH University of Science and Technology (Krakow), the State Agrarian and Engineering University in Podilya, the University of Žilina, the International Commission of Agricultural and Biosystems Engineering (CIGR) and the Polish Society of Agricultural Engineering. Honorary auspices were made by the Ministry of Science and Higher Education of the Republic of Poland, the rector of the University of Agriculture in Krakow, the rector of the AGH University of Science and Technology and the rector of the State Agrarian and Engineering University in Podilya.